Local Good-λ Estimate for the Sharp Maximal Function and Weighted Morrey Space - Yasuo Komori-Furuya (Journal of Function Spaces)
We give a characterization of weighted Morrey space by using Fefferman and Stein’s sharp maximal function. For this purpose, we consider a local good-λ inequality.